Quantifying the electrical transport characteristics of electron-doped La0.7Ce0.3MnO3 thin films through hopping energies, Mn valence, and carrier localization length. (May 2015) - Thiessen, A.; Beyreuther, E.; Werner, R.; Koelle, D.; Kleiner, R.; Eng, L.M.
Abstract: Cerium-doped LaMnO3 is widely discussed as one of the most prospective electron-doped thin-film prototype material that complements well-established hole-doped mixed-valence manganites. Here, we investigate La0.7 Ce0.3 MnO3 films with respect to their electrical properties and check whether they provide an effective electron doping with Mn-valences well below +3. Thin films of a variable thickness between 10 and 100 nm are characterized through resistance measurements over a broad temperature range between 90 and 300 K deducing their hopping energies, carrier localization lengths, and the Mn valence by comparing the experimental data to different transport models. While electronic transport above 300 K is well determined by the thermally activated diffusion of small polarons, we find the carrier localization by disorder to reveal a variable-range hopping-type transport for lower temperatures. From the several parameters investigated in the study, it is mainly the oxygen content and the degree of CeO2 phase segregation that are crucial to be controlled in such electron-doped thin-film manganites. Abstract : Highlights: The resistance of La0.7 Ce0.3 MnO3 films was investigated over a broad temperature range. Depending on the state of oxygen content, different hopping types were identified. Furthermore, the degree of CeO2 phase segregation is crucial for the transport. A number of the so far unknown electrical parameters were quantified for this compound.